Linking Trace Organic Contaminants in On‐Site Wastewater‐Treatment Discharge with Biological Effects. (12th October 2021) - Warren, Les D.; Guyader, Meaghan E.; Kiesling, Richard L.; Higgins, Christopher P.; Schoenfuss, Heiko L.
Abstract: Around the globe, on‐site wastewater‐treatment systems (OWTSs) are critical for rural communities without access to a municipal sewer system. However, their treatment efficiency does not match that of modern wastewater‐treatment plants. The impact of OWTS discharge on nearby aquatic ecosystems and their resident fish species is poorly understood. In the present study, larval and adult fathead minnows ( Pimephales promelas ) and adult sunfish ( Lepomis macrochirus ) were exposed for 21 days to two trace organic contaminant (TOrC) mixtures replicating water chemistry derived from a previous environmental study. Larval fathead minnows were assessed for survival, growth, predator avoidance, and feeding efficiency. Adult fathead minnows and sunfish were assessed for a suite of physiological endpoints (condition indices, vitellogenin, glucose), histological changes, and fecundity. The only observed effect of TOrC mixture exposure on larval fathead minnows was a decrease in feeding efficiency. Effects were mixed in exposed adult fishes, except for male sunfish which realized a significant induction of vitellogenin ( p  < 0.05). The consequences of TOrC mixture exposure in the present controlled laboratory study match effects observed in wild‐caught sunfish in a corresponding field study. The present study begins to bridge the gap by connecting nonpoint OWTS pollution with biological effects observed in resident lake fish species. Given the effects observed despite the brevity of the laboratory mixture exposure, longer‐term studies are warranted to understand the full impacts of OWTS discharge to nearby aquatic ecosystems.   Environ Toxicol Chem 2021;40:3193–3204. © 2021 SETAC. This article has been contributed to by US Government employees and their work is in the public domain in the USA.